Imatinib accelerates progenitor cell‐mediated liver regeneration in choline‐deficient ethionine‐supplemented diet‐fed mice. Issue 5 (5th December 2016) - Rókusz, András; Bugyik, Edina; Szabó, Vanessza; Szücs, Armanda; Paku, Sándor; Nagy, Péter; Dezső, Katalin
Summary: Severe chronic hepatic injury can induce complex reparative processes. Ductular reaction and the appearance of small hepatocytes are standard components of this response, which is thought to have both adverse (e.g. fibrosis, carcinogenesis) and beneficial (regeneration) consequences. This complex tissue reaction is regulated by orchestrated cytokine action. We have investigated the influence of the tyrosine kinase inhibitor imatinib on a regenerative process. Ductular reaction was induced in mice by the widely used choline‐deficient ethionine‐supplemented diet (CDE). Test animals were treated daily with imatinib. After 6 weeks of treatment, imatinib successfully reduced the extent of ductular reaction and fibrosis in the CDE model. Furthermore, the number of small hepatocytes increased, and these cells had high proliferative activity, were positive for hepatocyte nuclear factor 4 and expressed high levels of albumin and peroxisome proliferator‐activated receptor alpha. The overall functional zonality of the hepatic parenchyma (cytochrome P450 2E1 and glucose 6 phosphatase activity; endogenous biotin content) was maintained. The expression of platelet‐derived growth factor receptor beta, which is the major target of imatinib, was downregulated. The anti‐fibrotic activity of imatinib has already been reported in several experimental models. Additionally, in the CDE model imatinib was able to enhance regeneration and preserve the functional arrangement of hepatic lobules. These results suggest that imatinib might promote the recovery of the liver following parenchymal injury through the inhibition of platelet‐derived growth factor receptor beta.